Cardiac Hemodynamic Features in Patients with Infective Endocarditis Complicated by Acute Heart Failure - Hanna B. Koltunova; Kostiantyn P. Chyzh; Oleksii A. Krykunov (Ukrainian Journal of Cardiovascular Surgery, 2024)
Infective endocarditis (IE) is a rare but devastating disease. The main complications of IE are heart failure (HF), sepsis (in particular, due to perivascular spread of infection), and embolic events, most often those of cerebral local-ization. The diagnosis of IE combines various factors that are not specific to IE when considered separately. Echocardiog-raphy remains the first-line imaging modality for the diagnosis of IE.The aim. To determine the features of intracardiac complications that occur in patients with IE at the preoperative stage using ultrasound diagnostics.Materials and methods. The study included clinical data of 120 patients with IE who underwent examination and treatment from 01/01/2019 to 06/30/2020 at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine. The diagnosis of IE was established in accordance with the modified Duke/Eu-ropean Society of Cardiology 2015 criteria. The mean age of the studied patients was 46.3 ± 1.37 (19-69 years).Results. A high rate of nosocomial factors in the development of the disease was determined: 49 (40.9%) cases, of which 15 (12.5%) cases and 25 (20.8%) cases were urological and general surgical interventions, respectively. Preopera-tive HF was found in 16 (13.3%) cases. In the group of patients with acute HF, cases of left heart valve disease with peri-annular complications dominated: 9 (56.3%) cases of abscesses and 3 (18.8%) cases of fistulae. Significant differences were found in the assessment of the cardiac index: in the group of patients with IE without signs of HF, the cardiac index was 4.9 ± 0.2, and in the group of patients with preoperative HF it was 3.7 ± 0.4 (p = 0.098). Patients with acute HF were characterized by a higher level of acute kidney injury (creatinine 168.2 ± 40.7 μmol/L, urea 13.3 ± 2.5 mmol/L).Conclusions. The obtained results indicate a high incidence of intracardiac complications in patients with IE, in par-ticular, those caused by nosocomial infections and medical interventions. Ultrasound diagnostics (echocardiography) is an important tool for detecting and monitoring intracardiac complications at the preoperative stage, which can affect the treatment strategy and prognosis. A thorough examination of a patient with IE allows to identify critical features of cardiac hemodynamic disorders and ensure timely cardiac surgery.